The Effect of Product Quality and Price with The Halal Label as a Moderating Variable on Purchasing Decisions Zoya Halal Cosmetics in Pekanbaru City - Masita Isnania; Rendra Wasnury; Marhadi Marhadi (Universitas Riau, 2022)
The purpose of this study is to determine the effect of product quality and price on purchase decisions for Zoya brand halal cosmetics in Pekanbaru, using halal labels as a moderating variable. The population in this study are consumers who have purchased and used Zoya cosmetics and are domiciled in the city of Pekanbaru. The sampling technique is non-probability sampling, with a total sample of 128 respondents. This study uses structural equation modeling with partial least squares (SEM-PLS) in analyzing the data. The results showed that product quality had a positive and significant effect on purchasing decisions. Price has a positive and significant effect on purchase decisions. As a moderating variable, the halal label strengthens the positive relationship between product quality and purchase decisions. Furthermore, the halal label acts as a moderator, weakening the negative relationship between price and purchase decision